The added value of coaching compared to a friendly discussion: Nsight from behavioral economics - Marina Psiloutsikou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - This paper addresses a criticism of coaching that is rather overlooked in the respective literature but highly discussed among clients. It is often claimed that coaching is nothing more than a chat among friends or colleagues and has, therefore, no added value for a potential customer. Design/methodology/approach - The paper draws on the respective interdisciplinary literature to identify limitations and biases that are present in general discussions with friends or colleagues but professional coaches should be trained to overcome. Findings - Questions and discussion are indeed at the core of a coaching session, thus bearing much resemblance to a friendly chat. However, the resemblance is superficial. In this paper ten main differences between a coaching session and a discussion with a non-expert are found and analyzed. They are grouped into three categories: Biases, Heuristics and Personal Limitations. Research limitations/implications - Further research will be needed to test empirically the use of input from behavioural economics as a basis for coaching and also to enrich it with additional factors. Moreover, practitioners can use the proposed factors to increase their effectiveness as well as to create a unique selling proposition for their business. Originality/value - The paper discusses specific skills and capabilities that a professional coach must have and provides significant implications for both researchers and practitioners.
Keywords: M12; M53; O15; 330; Coaching; Added Value; Behavioral Economics; Biases; Heuristics